2017
DOI: 10.1016/j.ttbdis.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative vertical transmission of Rickettsia by Dermacentor variabilis and Amblyomma maculatum

Abstract: The geographical overlap of multiple Rickettsia and tick species coincides with the molecular detection of a variety of rickettsial agents in what may be novel tick hosts. However, little is known concerning transmissibility of rickettsial species by various tick hosts. To examine the vertical transmission potential between select tick and rickettsial species, two sympatric species of ticks, Dermacentor variabilis and Amblyomma maculatum, were exposed to five different rickettsial species, including Rickettsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…In horizontal acquisition, ticks imbibe an infectious bloodmeal from the vertebrate host, allowing the rickettsiae to enter the gut and then, through undefined mechanisms, disseminate throughout the tick to infect organs central to transmission, including the ovaries (vertical) and salivary glands (horizontal). The ability of individual Rickettsia species to successfully infect and be transmitted by a tick host varies by both Rickettsia and tick species ( 1 ). Transmission of SFG Rickettsia to a vertebrate host during tick feeding can result in disease ranging from a mild, self-limiting infection to death ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In horizontal acquisition, ticks imbibe an infectious bloodmeal from the vertebrate host, allowing the rickettsiae to enter the gut and then, through undefined mechanisms, disseminate throughout the tick to infect organs central to transmission, including the ovaries (vertical) and salivary glands (horizontal). The ability of individual Rickettsia species to successfully infect and be transmitted by a tick host varies by both Rickettsia and tick species ( 1 ). Transmission of SFG Rickettsia to a vertebrate host during tick feeding can result in disease ranging from a mild, self-limiting infection to death ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…are involved in preventing A. limbatum from moving south. Rickettsia can be transmitted via several pathways (transovarially, transtadially and horizontally), and transmission is dependent on the pathogen and the viability of its vector and host (Harris et al, 2017). Studies on the transmission of R. honei in B. hydrosauri ticks from Flinders Island, Tasmania, showed that Rickettsia is located in the oocytes, immature eggs, Malpighian tubules, midgut epithelium and salivary glands – suggestive of transovarial and horizontal transmission (Stenos et al, 2003; Whitworth et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Rickettsia spp. have been found to alter host animal behaviour and fitness such as influencing dispersal and thermal tolerance, egg production, moulting success and offspring viability in tick hosts (Harris et al, 2017). Crucially, in one study, R. rickettsii was found to be lethal to its tick vector Dermacentor andersoni following both vertical and horizontal transmission (Niebylski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated the occurrence of transovarial transmission in only a limited number of species [ 11 ]. Moreover, the efficiency of vertical transmission varies according to the rickettsial and tick species [ 19 , 34 ], and transmission may not occur in female ticks infected by sexual/co-feeding transmission [ 35 ]. Vertebrate hosts may thus be necessary to maintain and perpetuate some rickettsial agents in nature [ 36 ].…”
Section: Rickettsia Spp Infection In Animalsmentioning
confidence: 99%